Intrinsic Motivation at Work and its relationship with the variables Goal Orientation and Tenacity - Solf-Zárate, Arturo (2006)
The relation between the Intrinsic Motivation at Work with the personality variables Goal Orientation and Tenacity (conscientiousness) was investigated, in order to replace the variable Growth Need of the motivational model proposed by Hackman and Oldham (1980). The instruments were applied to a sample of employees (N = 228) of a textile company pertaining to 60 different positions. The results showed that the Intrinsic Motivation at Work presented a positive relation with the Goal Orientation centered in the Learning (r = 0.43; p < ,01). Finally one provides suggestions for future investigation on the subject, and with aims of application in the scope of the administration of the Human Resources.